Physicochemical, rheological and morphological properties of bitumen incorporating petroleum sludge - Memon, A.M. (Elsevier Ltd, 2021)
Crude oil refining processes generate a large amount of petroleum sludge (PS) in petroleum industries. Globally, PS has gained widespread attention to ensure its effective waste management. This study investigated the suitability of PS to provide an alternative bitumen modification and reduce waste accumulation in petroleum industries. The effects of PS content on bitumen were analyzed using rotational viscometer (RV), storage stability, dynamic shear rheometer (DSR), gas chromatography-mass spectrometry (GCâMS), Fourier transform infrared spectroscopy (FTIR), and atomic force microscopy (AFM) characterization. The GCâMS and storage stability characterization validated a good compatibility between PS and bitumen. Rheological characterization showed that 8 PS content tends to improve the fatigue resistance, keeping into consideration the rutting resistance of bitumen. The presence of lightweight hydrocarbons in PS was responsible for the performance improvement of bitumen, as indicated by the functional groups and aging recognition in FTIR. Surface topography and phase images indicated a reduction in bee structures due to the presence of lightweight hydrocarbons in PS. Based on the findings of this study, PS can be used for the production of bitumen, thereby reducing the risk of waste accumulation in petroleum industries. Â© 2021 Elsevier Ltd